Abroad Migration and Rural Livelihoods: Evidence from Smallholder Farmers in Kavrepalanchowk District, Nepal - Dhungel, Sunil; Dhakal, Saroj (Journal of the Institute of Agriculture and Animal Science, 2025)
Labor migration and remittances play a pivotal role in shaping the livelihoods of smallholder farmers in Nepal. The study examines how structural, economic and social factors influence migration decision and how remittance contribute to household welfare. A mixed-methods design was employed, drawing on survey data from 100 households-50 with at least one family member migrating and 50 without- supplemented by focus group discussion and key informant interviews. Binary logistic regression model was used to identify determinants of migration, while independent-sample t-tests and Chi-square test compared the outcomes between households. Findings indicated that migration decision is driven by both push factors, such as indebtedness and financial obligations and pull factors, such as perceived higher income abroad. Larger landholdings decrease the likelihood of migration (β = −0.208, p = 0.030), whereas outstanding loans (β = 2.837, p = 0.002) and solo financial responsibility (β = 2.354, p = 0.002) significantly increased migration likelihood. A positive perception for abroad opportunities is also raised the odds of migration ((β = 1.522, p = 0.049). Moreover, migrant households demonstrating significantly higher annual incomes and spent more on quality food, education, healthcare, sanitation and productive assets- demonstrating the transformative potential of remittance in strengthening physical, human and financial capital. These findings underscore migration for abroad employment as both a coping strategy in response to economic stress and as an aspirational pathway for resource accumulation and human capital development. Nevertheless, migration often appears as a necessity driven by economic pressure rather than long-term planned livelihood strategy.